Gypsum plastering thixotropic agent and preparation method thereof
By scientifically combining water retention, thixotropy, lubrication and inorganic components, a gypsum plaster thixotropic agent was prepared, which solved the shortcomings of existing products in terms of water sensitivity, smoothness and anti-sagging ability, and achieved Better construction performance and cost-effectiveness.
Patent Information
- Application Number
- CN202411403196.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing gypsum plaster thixotropic agents have shortcomings in terms of water sensitivity, smoothness and anti-sagging ability, and are expensive and difficult to meet market demand.
Using scientific combination of water-retaining components, thixotropic components, lubricating components and inorganic components, including polyacrylamide, tapioca starch, sodium hydroxypropyl starch, etc., it is uniformly mixed through a dry powder mixer to prepare a Gypsum plaster thixotropic agent.
It significantly improves the thixotropic performance, sag resistance and consistency of plaster gypsum mortar, ensures the sag resistance stability within the range of 3%-5% of the water consumption, and reduces the cost of the product.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of gypsum thixotropic agent preparation, and particularly relates to a gypsum plaster thixotropic agent and a preparation method thereof. Background Art
[0002] With the need for the development of green building materials in China, gypsum-based building materials have gradually diversified from single gypsum board applications to self-leveling materials, plastering and other application fields. Unlike cement-based plastering mortar, which uses high air entrainment, strong plasticization, high water retention, and long slow setting, plastering gypsum uses premixes to mix with water at the construction site, and the construction will be completed within 30 minutes after the production is completed. The plastering gypsum has almost no shrinkage performance, which greatly reduces the risk of hollowing and cracking of the plastering gypsum. The most critical material in gypsum-based plastering is thixotropic agent, which gives gypsum plastering good anti-sagging performance and smoothness of scraping. It is smooth and dense under pressure without drawing or sticking to the knife, and does not sag or deform in a static state, which can well meet the needs of wall leveling.
[0003] Traditional thixotropic agents are mostly single-component starch ethers, which usually only meet certain indicators of construction requirements. For example, materials with good anti-sagging performance usually lack smoothness during construction, materials with good smoothness usually have poor anti-sagging ability, or materials that require both performance are particularly sensitive to water use, and will lose anti-sagging ability if the water consumption on the construction site is not well controlled. The products with the best feedback on the market are often imported starch ether products, but they are very expensive. Therefore, it is urgent to develop a gypsum-based thixotropic agent solution that has a wide range of water use, excellent thixotropy, and good anti-sagging performance. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the present invention provides a gypsum plaster thixotropic agent and a preparation method thereof, which can significantly improve the smoothness, thixotropic properties, anti-sagging properties of the plaster gypsum mortar, as well as the good consistency retention over time for 30 minutes and the anti-sagging stability when the water consumption fluctuates within the range of 3%-5%.
[0005] To achieve the above purpose, the technical solution adopted by the present invention to solve the technical problem is: A gypsum plaster thixotropic agent comprises the following components in parts by weight: 8 to 15 parts of water-retaining component, 25 to 50 parts of thixotropic component, 3 to 10 parts of lubricating component and 25 to 64 parts of inorganic component.
[0006] Further, the following components are included in parts by weight: 8 to 10 parts of water-retaining component, 30 to 50 parts of thixotropic component, 5 to 10 parts of lubricating component and 25 to 50 parts of inorganic component.
[0007] Furthermore, the water-retaining component includes at least one of polyacrylamide and sodium polyacrylate water-absorbing resin with molecular weights of 8 million, 16 million, and 25 million, respectively.
[0008] Further, the thixotropic component includes at least one of tapioca starch, sodium hydroxypropyl starch, sodium carboxymethyl starch, hydroxyethyl starch ether, sodium octenyl succinate starch and hydroxypropyl distarch phosphate.
[0009] Furthermore, the thixotropic component includes cassava starch, hydroxyethyl starch ether and sodium starch octenyl succinate in a mass ratio of 20-25:5-10:1-5.
[0010] Furthermore, the thixotropic component includes sodium carboxymethyl starch and hydroxypropyl distarch phosphate in a mass ratio of 1-3:0.5-1.
[0011] Further, the lubricating component includes at least one of redispersible latex powder VAE, hydroxypropyl methylcellulose ether 400 and polyethylene glycol 4000.
[0012] Furthermore, the inorganic component includes at least one of refined sepiolite powder, sodium bentonite, magnesium aluminum silicate and attapulgite clay powder.
[0013] The preparation method of the gypsum plaster thixotropic agent comprises mixing the components uniformly according to the formula.
[0014] Beneficial effects of the present invention: 1. By scientifically matching the three core components of water retention, thixotropy and lubrication, the properties of organic and inorganic substances complement each other, and their respective properties are brought into play to the maximum extent, significantly improving the thixotropic properties and anti-sagging properties of the plaster gypsum mortar. Commonly used water-retaining agents are high molecular weight polymers. While improving the water retention capacity, they will also increase the viscosity of the system, affecting the smoothness and surface flatness of the construction. The present invention creatively adds polyethylene glycol (PEG) to the formula, so that the plaster gypsum obtains the corresponding smoothness and surface gloss, ensuring good construction performance and reducing the phenomenon of sticking to the knife and drawing. It effectively solves the shortcomings of traditional products that are sensitive to water consumption and cannot take into account both smoothness and anti-sagging capabilities, so that the products prepared by the present invention have better construction capabilities.
[0015] 2. The use of polyacrylamide and sodium polyacrylate water-absorbing resin makes the plaster gypsum system have a strong water-retaining function, so that the water is almost completely locked inside the plaster gypsum, and the internal water will not be lost due to external high temperature, dryness and other factors, thereby ensuring the good consistency retention over time for 30 minutes. Traditional products will cause sagging and cannot be used if 1% to 2% more is used under the appropriate water consumption of gypsum plastering. The addition of water-retaining components can effectively reduce the sensitivity of water use, so that the anti-sagging property of the plaster gypsum system is almost unaffected when the total water consumption fluctuates within the range of 3%-5%, thereby obtaining better anti-sagging stability and still having good anti-sagging ability. The present invention can better balance the viscosity of the system by using a combination of anionic polyacrylamides of different molecular weights.
[0016] 3. The thixotropic component is a combination of various organic substances with thixotropic ability, which can adapt to the requirements of phosphogypsum and desulfurized gypsum in different acid environments. The inorganic component is an excellent porous interwoven mineral structure, which usually also has certain thixotropic and suspension capabilities. The combination of organic and inorganic substances can effectively control the overall cost, and has better adaptability to gypsum. The product is not easy to thicken and has excellent thixotropic properties. DETAILED DESCRIPTION
[0017] The specific implementation modes of the present invention are described below so that those skilled in the art can understand the present invention. However, it should be clear that the present invention is not limited to the scope of the specific implementation modes. For those of ordinary skill in the art, as long as various changes are within the spirit and scope of the present invention as defined and determined by the attached claims, these changes are obvious, and all inventions and creations utilizing the concept of the present invention are protected.
[0018] Example 1 A gypsum plaster thixotropic agent comprises the following components in parts by weight: 9 parts of anionic polyacrylamide 800w, 3 parts of anionic polyacrylamide 1600w, 20 parts of tapioca starch, 20 parts of sodium carboxymethyl starch, 8 parts of sodium starch octenylsuccinate, 4 parts of PEG4000, 2 parts of VAE, 28 parts of sodium bentonite and 6 parts of refined sepiolite powder.
[0019] The above components are mixed evenly using a dry powder mixer, with each raw material added at an interval of 30-40 seconds, and then stirred and mixed for 15 minutes after the addition is completed, so as to obtain the gypsum plaster thixotropic agent.
[0020] Example 2 A gypsum plaster thixotropic agent comprises the following components in parts by weight: 9 parts of anionic polyacrylamide 800w, 3 parts of anionic polyacrylamide 2500w, 30 parts of sodium carboxymethyl starch, 10 parts of hydroxypropyl distarch phosphate, 4 parts of PEG4000, 2 parts of HPMC400, 30 parts of sodium bentonite and 12 parts of magnesium aluminum silicate.
[0021] The above components are mixed evenly using a dry powder mixer, with each raw material added at an interval of 30-40 seconds, and then stirred and mixed for 15 minutes after the addition is completed, so as to obtain the gypsum plaster thixotropic agent.
[0022] Example 3 A gypsum plaster thixotropic agent comprises the following components in parts by weight: 11 parts of anionic polyacrylamide 1600w, 25 parts of sodium carboxymethyl starch, 20 parts of hydroxyethyl starch ether, 3 parts of VAE, 3 parts of HPMC400, 25 parts of sodium bentonite and 13 parts of attapulgite powder.
[0023] The above components are mixed evenly using a dry powder mixer, with each raw material added at an interval of 30-40 seconds, and then stirred and mixed for 15 minutes after the addition is completed, so as to obtain the gypsum plaster thixotropic agent.
[0024] Example 4 A gypsum plaster thixotropic agent comprises the following components in parts by weight: 9 parts of anionic polyacrylamide 800w, 3 parts of sodium polyacrylate water-absorbing resin, 25 parts of tapioca starch, 10 parts of hydroxyethyl starch ether, 3 parts of sodium octenyl succinate starch, 6 parts of PEG4000 and 44 parts of sodium bentonite.
[0025] The above components are mixed evenly using a dry powder mixer, with each raw material added at an interval of 30-40 seconds, and then stirred and mixed for 15 minutes after the addition is completed, so as to obtain the gypsum plaster thixotropic agent.
[0026] Example 5 A gypsum plaster thixotropic agent comprises the following components in parts by weight: 6 parts of anionic polyacrylamide 800w, 2 parts of anionic polyacrylamide 1600w, 2 parts of anionic polyacrylamide 2500w, 25 parts of sodium carboxymethyl starch, 5 parts of sodium hydroxypropyl starch, 10 parts of hydroxyethyl starch ether, 2 parts of PEG4000, 2 parts of VAE, 2 parts of HPMC400, 24 parts of sodium bentonite, 10 parts of magnesium aluminum silicate and 10 parts of sepiolite powder.
[0027] The above components are mixed evenly using a dry powder mixer, with each raw material added at an interval of 30-40 seconds, and then stirred and mixed for 15 minutes after the addition is completed, so as to obtain the gypsum plaster thixotropic agent.
[0028] Experimental testing The ingredients per ton of plastering gypsum are as follows: 595.0Kg of gypsum (Shandong Xinfa), 200.0Kg of 40-70 mesh natural sand, 200.0Kg of 70-120 mesh natural sand, 3.5kg of hydroxypropyl methylcellulose ether 8w, 1.5Kg of gypsum retarder (Shenhui Refining). The plastering gypsum mortars are measured according to the standard diffusion water content determination method in 7.4.2.1 of GB / T 28627-2012 "Plastering Gypsum" to obtain the corresponding standard diffusion water content, and the corresponding standard diffusion (165±5mm) bottom plastering gypsum mortar is made according to the prescribed method.
[0029] 1. Thixotropic performance test The thixotropic agent prepared in Example 1 was used in an amount of 1‰ to prepare a bottom plaster gypsum mortar as a reference sample. The prepared bottom plaster gypsum mortar was tested using an NDJ-8S rotational viscometer, and its viscosity was measured at shear rates of 6 rpm and 60 rpm, respectively. The ratio of the two viscosity values was used as the thixotropic index of the bottom plaster gypsum mortar. The larger the index, the better the thixotropy.
[0030] 2. Anti-sagging plaster fall value test Place the concrete slab horizontally, fix the test plaster frame on the concrete slab, and manually plaster the sample prepared according to the standard diffusion water consumption in the plastering area (plastering area is 35cmx35cm, plastering thickness is 20mm), then carefully remove the frame and place the concrete slab vertically. The operation time of placing the concrete slab vertically from the contact of the slurry to the end of plastering should be controlled within 6 minutes. 15 minutes after the concrete slab is placed vertically, use a steel ruler to measure the minimum distance from the bottom edge of the concrete slab to the bottom edge of the sample and record it as (d), accurate to 0.1mm. The smaller the drop value, the better. Generally, a drop value greater than 10.0mm does not have construction capacity.
[0031] 3. Fluency test (applicability and combability) Using cement board as the base material and simulating construction operations, there should be no hanging of the knife and no curling.
[0032] 4. Consistency detection The determination method of initial consistency value and 30-minute consistency value refers to the consistency test in Article 4 of the JGJ / T70-2009 "Test Method for Basic Properties of Building Mortar" standard. The smaller the consistency data, the greater the consistency.
[0033] 5. Water consumption sensitivity test The product of Example 4 was tested by using 3% more water than the standard water consumption.
[0034] The test results of items 1 to 5 above are shown in Table 1.
[0035] Table 1 Thixotropic agent properties CASUCOL 301 Example 1 Example 2 Example 3 Example 4 Example 5 Example 4: excess water content 3% Drop value d (mm) 3.1 6.7 4.3 3.7 3.0 4.1 4.8 Feel Good shaping, non-sticky material, smooth application, good surface gloss The shaping is average, the material is not sticky and can be applied smoothly, and the surface is glossy Good shaping, smooth application, slight hair pulling, good surface gloss Good shaping, average smearing smoothness, poor surface gloss Good shaping, non-sticky material, smooth application, good surface gloss The shaping is average, the material is sticky, the application is smooth, and the surface gloss is good Good shaping, non-sticky material, smooth application, good surface gloss Initial consistency (mm) 85 88 81 75 84 77 89 Time consistency 30min (mm) 78 80 76 69 79 72 80 Thixotropic index 6.3 5.5 6.2 5.7 6.4 5.9 6.0 According to the test results in Table 1, the gypsum plaster thixotropic agent prepared by the present invention can effectively resist sagging, has a wide range of water use, and has a smooth feel and excellent thixotropic performance. Among them, Example 4 has the best effect, and the effect is basically equivalent to that of Avibe. Although Examples 1, 2, 3, and 5 also have certain anti-sagging properties, due to the different selection and combination of the water-retaining components, thixotropic components, etc., their efficacy is significantly different from that of Example 4 of this scheme, and is not as good as that of the prior art Avibe as a comparison.
[0036] In addition, different technical schemes are constructed by selecting different ingredients for the thixotropic components in Examples 1 to 5, but according to the records in Table 1, only the thixotropic performance of the technical scheme recorded in Example 4 is comparable to that of the prior art Avibe as a comparison, and is even slightly better in performance. The thixotropic performance of products prepared by other combinations is significantly inferior to that of this scheme and Avibe. Moreover, the cost of the technical scheme in Example 4 is less than half of that of the imported product Avibe. It can be seen that the thixotropic agent prepared by the technical scheme constructed by the present invention not only has excellent anti-sagging, a wide range of water use, good thixotropy and other characteristics, but also its cost is much lower than that of imported products, and is more suitable for production and promotion.
[0037] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A gypsum plaster thixotropic agent, characterized in that: The composition comprises the following components in parts by weight: 8 to 15 parts of water-retaining component, 25 to 50 parts of thixotropic component, 3 to 10 parts of lubricating component and 25 to 64 parts of inorganic component.
2. The gypsum plaster thixotropic agent according to claim 1, characterized in that The composition comprises the following components in parts by weight: 8 to 10 parts of water-retaining component, 30 to 50 parts of thixotropic component, 5 to 10 parts of lubricating component and 25 to 50 parts of inorganic component.
3. The gypsum plaster thixotropic agent according to claim 1 or 2, characterized in that The water-retaining component includes at least one of polyacrylamide and sodium polyacrylate water-absorbing resin with molecular weights of 8 million, 16 million and 25 million respectively.
4. The gypsum plaster thixotropic agent according to claim 1 or 2, characterized in that The thixotropic component includes at least one of tapioca starch, sodium hydroxypropyl starch, sodium carboxymethyl starch, hydroxyethyl starch ether, sodium octenyl succinate starch and hydroxypropyl distarch phosphate.
5. The gypsum plaster thixotropic agent according to claim 4, characterized in that The thixotropic component comprises cassava starch, hydroxyethyl starch ether and sodium starch octenyl succinate in a mass ratio of 20-25:5-10:1-5.
6. The gypsum plaster thixotropic agent according to claim 4, characterized in that The thixotropic component comprises sodium carboxymethyl starch and hydroxypropyl distarch phosphate in a mass ratio of 1-3:0.5-1.
7. The gypsum plaster thixotropic agent according to claim 1 or 2, characterized in that The lubricating component includes at least one of redispersible latex powder VAE, hydroxypropyl methylcellulose ether 400 and polyethylene glycol 4000.
8. The gypsum plaster thixotropic agent according to claim 1 or 2, characterized in that The inorganic component comprises at least one of refined sepiolite powder, sodium bentonite, magnesium aluminum silicate and attapulgite clay powder.
9. The method for preparing the gypsum plaster thixotropic agent according to any one of claims 1 to 8, characterized in that: Mix all the components evenly according to the formula.